2021
DOI: 10.2319/030821-184.1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of platelet rich fibrin versus demineralized bone xenograft in periodontally accelerated osteogenic orthodontics:

Abstract: Objectives To compare the rate of extraction space closure between periodontally accelerated osteogenic orthodontics (PAOO) using platelet-rich fibrin (PRF) (Group 1) and PAOO using demineralized bone xenograft (DMBM) (Group 2) and to compare the level of wound healing between the PRF group vs the DMBM group after PAOO. Materials and Methods A two-arm prospective single blind pilot study with a split-mouth design was used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Exploring this aspect could be a future scope for comparison as augmentation with materials like platelet-rich fibrin and bone-grafts has demonstrated synergistic effects. 16 , 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploring this aspect could be a future scope for comparison as augmentation with materials like platelet-rich fibrin and bone-grafts has demonstrated synergistic effects. 16 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…The level of statistical significance level was set at p≤0.05. 16 This parallel arm study was approved by the Institute’s Scientific Review Board and Ethical Committee of SRM Dental College (approval no: SRMDC/IRB/2019/MDS/No.108A, date: 04.01.2022) and was registered under the Clinical Trial Registry. The study was designed as a preliminary parallel-arm investigation following a split mouth study design, where one quadrant of the maxillary arch served as the corticotomy side and the opposite side serving as the control ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is rich in platelets, white blood cells, mononuclear cells, and various cytokines, with advantages such as simple preparation, no immunogenicity, and easy clinical application [ 76 , 77 ]. In vitro, studies have shown that PRF exhibits properties such as promoting angiogenesis and has achieved good results when used in conjunction with xenografts in studies on ARP, guided bone regeneration, periodontal regeneration, MSFE, and accelerated orthodontic tooth movement [ 15 , 46 , 78 , 79 , 80 , 81 ]. Studies have found that different centrifugal processes may alter the 3D network structure of PRF, which may potentially affect the efficacy of related bone-augmentation techniques [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, studies have shown that PRF exhibits properties such as promoting angiogenesis and has achieved good results when used in conjunction with xenografts in studies on ARP, guided bone regeneration, periodontal regeneration, MSFE, and accelerated orthodontic tooth movement [ 15 , 46 , 78 , 79 , 80 , 81 ]. Studies have found that different centrifugal processes may alter the 3D network structure of PRF, which may potentially affect the efficacy of related bone-augmentation techniques [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. Based on the above background, PRF has great research potential in enhancing the performance of bone xenografts and is one of the future research hotspots.…”
Section: Discussionmentioning
confidence: 99%